Novel Perspectives on the Hepatitis B Virus Vaccine in the Chronic Kidney Disease Population. Issue 12 (December 2015) - Fabrizi, Fabrizio; Martin, Paul; Messa, Piergiorgio
Background: The prevalence and incidence rates of hepatitis B virus (HBV) among patients undergoing maintenance dialysis in developed countries have declined over the last 2 decades thanks to the implementation of numerous infection control procedures in dialysis units, including the hepatitis B vaccine. It is well known that the immune response against HBV vaccine is unsatisfactory in the chronic kidney disease (CKD) population. The seroprotection rate after the HB vaccine schedule is low and the anti-HB titers are reduced, falling logarithmically over time. Purpose: We did an extensive review of the medical literature on the mechanisms underlying the reduced response rate towards the HBV vaccine in patients with CKD. The efficacy and safety of HBV vaccines for use in the CKD population was also evaluated. Results: Currently available vaccines against HBV are mostly plasma-derived or manufactured by recombinant DNA technology (yielding the S protein of the HBV envelope). The most promising strategy to enhance the immune response toward the HBV vaccine in the dialysis population is given by adjuvanted vaccines. Second-generation recombinant HB vaccines provided with a novel adjuvant (AS04, made of 3- O -4′-desacyl-monophosphoryl lipid A adsorbed on aluminum phosphate) demonstrated improved immunogenicity but a number of patients with an unsatisfactory response still occurs. Additional second-generation vaccines containing nonaluminum-based adjuvant systems such as AS02 (3- O -desacyl-4′-monophoshoryl lipid A and QS21) or 1018 (a Toll-like receptor 9 agonist) have shown higher immunogenicity and acceptable safety in the CKD population. The evidence in patients with end-stage renal disease is extremely limited on the use of third-generation vaccines, recombinant HBV vaccines expressed in mammalian cells containing S/Pre-S antigens. Conclusions: The immunogenicity of HBV vaccines in patients with CKD is suboptimal but novel technologies promise to give better results in the near future.